Qur’anic Ethical Frameworks of Consumption and Implications for Contemporary Ecological Thought - Ahmad Ghufron Fawaid; Nikmatu Rohmah; Triya Ayu Safitri; Moh. Faishal Haq (Journal of Islamic Thought and Contemporary Studies, 2025)
Islamic ethics of consumption has become increasingly important in the modern era, as contemporary consumption patterns are shaped by materialistic tendencies and excessive lifestyles that contribute to social and ecological degradation. This study aims to examine the value of moderation in consumption as articulated in Qur’an Surah al-Furqan verse 67 and to explore its relevance to contemporary consumer challenges. Using a thematic tafsir analysis that integrates insights from both classical and contemporary exegetes, this research highlights the prohibition of israf and tabdzir as well as the affirmation of balance as foundational principles for responsible consumption. The findings indicate that the verse provides not only moral–spiritual guidance but also a practical ethical framework for resource management and the regulation of modern consumer behavior. The novelty of this study lies in its direct linkage between Qur’anic moderation and today’s ecological and social challenges, demonstrating that Qur’anic ethics of consumption offers strategic implications for shaping sustainable lifestyles.